The Atacama Cosmology Telescope: temperature and gravitational lensing power spectrum measurements from three seasons of data - Das, S; Louis, T; Nolta, MR; Addison, G; Battistelli, E; Bond, JR; Calabrese, E; Crichton, D; Devlin, M; Dicker, S; Dunkley, J; Duenner, R; et al. (2014)
We present the temperature power spectra of the cosmic microwave background (CMB) derived from the three seasons of data from the Atacama Cosmology Telescope (ACT) at 148 GHz and 218 GHz, as well as the cross-frequency spectrum between the two channels. We detect and correct for contamination due to the Galactic cirrus in our equatorial maps. We present the results of a number of tests for possible systematic error and conclude that any effects are not significant compared to the statistical errors we quote. Where they overlap, we cross-correlate the ACT and the South Pole Telescope (SPT) maps and show they are consistent. The measurements of higher-order peaks in the CMB power spectrum provide an additional test of the ΛCDM cosmological model, and help constrain extensions beyond the standard model. The small angular scale power spectrum also provides constraining power on the Sunyaev-Zel'dovich effects and extragalactic foregrounds. We also present a measurement of the CMB gravitational lensing convergence power spectrum at 4.6σ detection significance. © 2014 IOP Publishing Ltd and Sissa Medialab srl.